Temporal variation of patch connectivity determines biodiversity recovery from recurrent disturbances - Jacquet, Claire; Munoz, François; Bonada, Núria; Thibault Datry; Heino, Jani; Jabot, Franck (bioRxiv, 2022)
Understanding the capacity of ecological systems to withstand and recover from disturbances is a major challenge for ecological research in the context of environmental change. Disturbances have multi-scale effects: they can cause species extinctions locally and alter connectivity between habitat patches at the metacommunity level. Yet, our understanding of how disturbances influence landscape connectivity remains limited. To fill this gap, we develop a novel connectivity index that integrates the temporal variation of patch connectivity induced by disturbances, which can be applied to any spatially-structured habitat. We then combine this index with a metacommunity model to specifically investigate biodiversity recovery from drying events in river network metacommunities. We demonstrate that patch connectivity explains variations of species richness between groups of organisms with contrasting dispersal modes and captures the effect of drying intensity (i.e., fraction of patches that dry-up) and drying location on community recovery. As a general rule, loss of patch connectivity decreases community recovery, regardless of patch location in the river network, dispersal mode, or drying intensity. Local communities of flying organisms maintained higher patch connectivity in drying river networks compared to organisms with strictly aquatic dispersal, which explained the higher recovery capacity of this group from drying events. The general relationship between patch connectivity and community recovery we found can be applied to any spatial network subject to temporal variation of connectivity, thus providing a powerful tool for biodiversity management in dynamic landscapes. Competing Interest Statement The authors have declared no competing interest.